PEMBERDAYAAN KOMUNITAS MASYARAKAT DALAM MENINGKATKAN MUTU PENDIDIKAN - Ilham Akbar Habibi, Ilham Akbar Habibi; Anita Anita, (UNISAN JURNAL, 2024)
School is a social institution that cannot be separated from its community environment, and vice versa. Both have interrelated interests. Schools act as formal institutions responsible for educating, training and guiding the nation's children, while the community is the stakeholder or user of educational services. The success of education does not only depend on the educational process at school and the availability of infrastructure, but is also influenced by the role of the family and community. Therefore, education is a shared responsibility between schools, families and society. Active community participation in schools is an indicator that school management is running well. When the government, in this case the school, collaborates harmoniously with the community and parents, this will have a significant impact on school progress and increasing student learning achievement, which is one measure of the quality of education. Efforts to involve the community in improving the quality of education in schools can be done in several ways. First, carry out outreach to formal leaders regarding the importance of the role of society in education. Second, involving formal leaders to take responsibility for schools or madrasas, because the development of these educational institutions will have an impact on the local community. Third, show direct programs that not only educate children, but also show the achievements that have been achieved by students, teachers, as well as the achievements of the school as a whole. This aims to show the community that their school is an integral part of developing quality education.